Stategi Pengendalian Perkembangan Permukiman Kumuh di Kasawan Lingkungan Mannaungi Kecamatan Turikale Kabupaten Maros - Rusneni Ruslan; Kristianto Erdiansyah Widodo; Rudi Latief (Fakultas Teknik Universitas Bosowa, 2021)
The purpose of this study is to identify the causes of the influence of the formation of slums and identify control strategies for the development of slums in the Mannaungi Environmental Area, Turikale District, Maros Regency. This study uses quantitative and qualitative research methods to identify influencing factors using chi square, while to formulate control strategies using SWOT analysis. The main conclusion of this study is that there are four factors that can influence the formation of slum settlements in the protected environmental area, namely family member factors, education factors, livelihood factors, and income factors on the formation of slum settlements in the Mannaungi Environmental Area, Turikale District, Maros Regency which has an influence on conditions. slums. While the factor of land ownership status has no effect on the formation of slum settlements in the area and the strategy used is to utilize public awareness in supporting the handling of slums through government programs related to the Minister of PUPR Regulation Number 2 of 2016, Development of residential areas based on Law no. 26 of 2007, and Utilizing the role of the government in Law Number 1 of 2011.